2023
DOI: 10.1021/acs.jafc.2c08004
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Quality Evaluation of Cultured Fat

Abstract: Cultured meat is rapidly developing as an emerging meat production technology. Adipose tissue plays an essential role in the flavor of meat products. In this study, cultured fat was produced by cultured adipose-derived stem cells (ADSCs) based on collagen in vitro, with a 3D model. The research showed that ADSCs could attach to collagen hydrogels and differentiate into mature adipocytes. Texture analysis demonstrated that the springiness, cohesiveness, and resilience of cultured fat were consistent with porcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Specifically, oxidative degradation and hydrolysis of lipids produce a variety of aldehydes, ketones, and acids such as hexanal, nonanal, and 2-heptenal. These compounds, along with esters, which were generated by esterification between free fatty acids and alcohols from lipid oxidation, including octanoic acid and ethyl ester, provided the basic fatty and oily flavors of fat tissue. Notably, heterocyclic compounds (pyrazine) and 1-hexanol, 2-ethyl-, contributors to roasted nut, bread, and green odor, were detected in cultured fat tissue with higher proportions compared to that of conventional porcine SAT. These molecules were generated from Maillard reactions between reducing sugars, probably from the basic culture medium, and amino acids from protein scaffolds and ECM macromolecules secreted by cells.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, oxidative degradation and hydrolysis of lipids produce a variety of aldehydes, ketones, and acids such as hexanal, nonanal, and 2-heptenal. These compounds, along with esters, which were generated by esterification between free fatty acids and alcohols from lipid oxidation, including octanoic acid and ethyl ester, provided the basic fatty and oily flavors of fat tissue. Notably, heterocyclic compounds (pyrazine) and 1-hexanol, 2-ethyl-, contributors to roasted nut, bread, and green odor, were detected in cultured fat tissue with higher proportions compared to that of conventional porcine SAT. These molecules were generated from Maillard reactions between reducing sugars, probably from the basic culture medium, and amino acids from protein scaffolds and ECM macromolecules secreted by cells.…”
Section: Resultsmentioning
confidence: 99%
“…There are more common types of plant viruses, such as, tobacco mosaic virus (TMV) [129,130], cucumber mosaic virus [131,132], tomato chlorotic virus [133,134], and tomato spotted wilt virus [135,136]. The use of chemical antiviral agents is currently one of the most effective methods of plant virus disease management [137][138][139][140]. Therefore, the discovery of novel antiviral agents is extremely important.…”
Section: Anti-plant Virus Activitymentioning
confidence: 99%
“…However, they revealed that it is challenging to mimic the taste of traditional meat in solely cultured tissue without any treatment due to the different amino acid composition. Liu et al also reported that cultured fat had fruity and creamy flavor characteristics due to the lipid oxidation of fatty acids formed in cultured fat 12 . Recently, our group revealed that the enhanced proliferation and differentiation of murine and bovine myoblasts could induce relatively more meat-like flavors in cultured meat 5 , 13 .…”
Section: Introductionmentioning
confidence: 98%